2021
DOI: 10.1111/jopr.13364
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of CAD/CAM Monolithic Lithium Disilicate Implant‐Supported Single Crowns Using Solid or Predrilled Blocks in a Fully Digital Workflow: A Retrospective Cohort Study With Up To 33 Months of Follow Up

Abstract: Purpose: To assess the clinical performance of CAD/CAM monolithic implantsupported restorations manufactured using a fully digital workflow and two different types of ceramic blocks. Materials and Methods: One hundred and one patients received single-unit implantsupported restorations at a University predoctoral clinic. All restorations were designed and fabricated using either a predrilled LS 2 block (group P, n = 59) or a conventional solid LS 2 block with an occlusal opening drilled manually prior to crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, another study with a 3-year follow-up using non-original Ti-base abutments reported biological complications during the observation period. Among the other studies using original Ti-base abutments, three studies reported biological complications free of implant suprastructures [43,49,50], and two retrospective caries studies reported a peri-implant mucositis rate of 6.8% at a mean follow-up of 18 months and 10.4% at 32 months [45,48].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, another study with a 3-year follow-up using non-original Ti-base abutments reported biological complications during the observation period. Among the other studies using original Ti-base abutments, three studies reported biological complications free of implant suprastructures [43,49,50], and two retrospective caries studies reported a peri-implant mucositis rate of 6.8% at a mean follow-up of 18 months and 10.4% at 32 months [45,48].…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year results from a study by Strauss et al reported the loss of 2 implants due to peri-implantitis, whereas 11 of the remaining 22 patients with implants were diagnosed with peri-implant mucositis [32]. The other two retrospective studies observed peri-implant mucositis in 6.8% and 10.4% of patients with implants during follow-up [45,48] (Table 5).…”
Section: Biological Complications and Peri-implant Health Parametersmentioning
confidence: 97%
See 3 more Smart Citations